2019
DOI: 10.1088/1742-6596/1341/2/022016
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of bacteria from mangrove sediment at coastal area in Pangkep South Sulawesi

Abstract: Mangrove ecosystem is an area with high potential of natural resourceswhich nowadaysremains unexplored. One of them is microorganismsthathidden in the depth of the mangrove sediments. Therefore, this study aims to isolate and characterize mangrove’s sediment bacteria from estuary coast of Pangkajene River, South Sulawesi, Indonesia. Sampling activities conducted at 6 stations with 3 different depths, those are 0-15 cm, 15-30 cm and 30-45 cm. Microbiological analysis includes microscopic, biochemical and analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…Our results suggested that the NA media is suitable for counting and isolating microbes from mangrove soil and sediments. This matches well with what was found by Ambeng et al, (2019), who used nutrient agar media to grow total colony counts from mangroves. In order to explore the fungi, the Potato Dextrose Agar medium for fungi was used by Ravikumar et al, (2004), and other researchers used Czapex dox (Thupurani et al, 2016).…”
Section: Preservationsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results suggested that the NA media is suitable for counting and isolating microbes from mangrove soil and sediments. This matches well with what was found by Ambeng et al, (2019), who used nutrient agar media to grow total colony counts from mangroves. In order to explore the fungi, the Potato Dextrose Agar medium for fungi was used by Ravikumar et al, (2004), and other researchers used Czapex dox (Thupurani et al, 2016).…”
Section: Preservationsupporting
confidence: 90%
“…Despite much research in this field, the results are somewhat conflicting and confusing. For example, some use nutrient agar for the growth of total colony counts from mangrove soil (Kumar et al, 2007;Ambeng et al, 2019) while some use Tryptic Soya Agar (TSA) (Pupin and Nahas, 2014).In comparison, others preferred Zobell's marine agar (ZB agar), and synthetic seawater media (Sakhia et al, 2016;Saravanakumar et al, 2016;Schut et al, 1993). Our results suggested that the NA media is suitable for counting and isolating microbes from mangrove soil and sediments.…”
Section: Preservationmentioning
confidence: 88%
“…Approximately 1 g of sediment and 1 mL of hot water samples were inoculated into 9 mL of each nutrient broth separately in a test tube and incubated at 55°C for 24 h. This was continued with serial dilution, spread on nutrient agar plates, and incubated at 60°C for 48 h. Bacterial colonies that grow on the agar surface were purified by stretching them to a new medium in a Petri plate and incubated for 48 h at 55°C (Ambeng et al 2019). The isolates were characterized morphologically and biochemically, including elevation, margin, color, Gram staining, catalase test, motility, triple sugar iron agar test, simmon citrate, and gelatinase.…”
Section: Bacterial Isolation and Characterizationmentioning
confidence: 99%
“…Bacteria is one kind of microorganisms, there are two groups of bacteria, they are archaebacteria and eubacteria (Sattley & Madigan, 2015), moreover, eubacteria/bacteria is more common and has various kind of their own group. These bacteria can also live in the soil as a decomposer, such as decomposer in mangrove soil (Chen et al, 2016;Sakhia et al, 2016;Wu et al, 2016;Ambeng et al, 2019). Recent study shows that bacteria live in mangrove soil to decompose mangrove litter and constantly live at there due to condusive environment to them for living.…”
Section: Microbiologymentioning
confidence: 99%
“…Recent study shows that bacteria live in mangrove soil to decompose mangrove litter and constantly live at there due to condusive environment to them for living. Some example mangrove bacteria are from genus Bacillus (Sakhia et al, 2016;Ambeng et al, 2019), Microccous, Yangia, Rhodococcus, Escherecia, Pseudotoromonas, Aerococcus, Pseudoteromonas (Sakhia et al, 2016), Staphylococcus, Vibrio, Alteromonas, Listeria, Macrococcus (Ambeng et al, 2019), Proteobacteria, Chloroflexi, Bacteriodetes, Planctomycetes (Wu et al, 2016). Those bacteria and mangrove soil can be potential learning sources for stundents.…”
Section: Microbiologymentioning
confidence: 99%